2021
DOI: 10.1186/s13293-021-00402-2
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in the expression of the endocannabinoid system within V1M cortex and PAG of Sprague Dawley rats

Abstract: Background Several chronic pain disorders, such as migraine and fibromyalgia, have an increased prevalence in the female population. The underlying mechanisms of this sex-biased prevalence have yet to be thoroughly documented, but could be related to endogenous differences in neuromodulators in pain networks, including the endocannabinoid system. The cellular endocannabinoid system comprises the endogenous lipid signals 2-AG (2-arachidonoylglycerol) and AEA (anandamide); the enzymes that synthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 113 publications
(105 reference statements)
2
18
0
Order By: Relevance
“…Our finding that female mice had higher expression of CB 1 Rs on GABAergic neurons than male mice was strongly supported by previous work (Levine et al., 2021). Levine revealed that CB 1 R staining on neurons in the vlPAG was much greater for females than males.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our finding that female mice had higher expression of CB 1 Rs on GABAergic neurons than male mice was strongly supported by previous work (Levine et al., 2021). Levine revealed that CB 1 R staining on neurons in the vlPAG was much greater for females than males.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, Levine et al. (2021) also found that 2‐AG, the most important retrograde signaling molecular, was lower in the female PAG compared to the male PAG (Levine et al., 2021). They also utilized immunohistochemical analysis to confirm that female mice had higher 2‐AG synthetic enzymes (DAGL), and 2‐AG hydrolyzing enzymes (MAGL and ABHD6), which may contribute to the decreased 2‐AG in female mice.…”
Section: Discussionmentioning
confidence: 99%
“…The 2-AG concentration was lower within the female PAG compared with the male PAG; this was confirmed using immunohistochemistry and proteomics. The observed sex differences in endogenous endocannabinoid mechanisms may in turn underlie the development of chronic pain conditions, as well as variations seen in therapy responses [ 366 ]. Sex differences in tolerance to THC were shown in mice with cisplatin-evoked chronic neuropathic pain [ 367 ].…”
Section: Sex-specific Differences In Ecs Ethical Considerations Of Ca...mentioning
confidence: 99%
“…These findings are consistent with Cupini et al [ 37 ], who detected a higher activity of FAAH and the AEA transporter in the platelets of female migraine patients than in males. In rodents, the ECS within pain modulatory pathways demonstrated sexual dimorphism, with significant differences between males and females in 2-AG and AEA concentrations [ 38 ]. Furthermore, it was suggested that sex differences in eCB ‘tone’ develop early, with growing pre-clinical evidence that gonadal hormones influence the expression of cannabinoid receptors and ligands, as well as their affinity and efficacy at receptors in various brain regions [ 39 ].…”
Section: Discussionmentioning
confidence: 99%